Effects of shank mass manipulation on sprinting techniques - Zhang, C.; Yu, B.; Yang, C.; Yu, J.; Sun, Y.; Wang, D.; Yin, K.; Zhuang, W.; Liu, Y. (Sports Biomechanics, 2022)
The purpose of this study was to determine the effects of shank mass manipulation on the sprinting technique in maximal-speed sprinting. Sixteen well-trained male athletes sprinted with and without an additional 15% of shank mass attached to the shank centre of mass. Kinematic data were collected using a 12-camera motion analysis system and analysed using linear regression analyses with categorical variables and paired t-tests. The sprinting speed (p < 0.01), knee flexion angle at landing (p = 0.028), and maximum hip flexion angular velocity (p = 0.029) decreased; contact time (p < 0.01) increased; and step length, step frequency, and other analysed technique measures of maximal-speed sprinting were unchanged (p = 0.12) with shank mass manipulation, compare with no manipulation. The relationships of sprinting speed with critical linear and angular kinematics at landing, take-off and swing in maximal-speed sprinting were not affected by the shank mass manipulation. These results suggest that 15% shank mass manipulation does not change the sprinting technique of well-trained male athletes in maximal-speed sprinting. This supports the use of shank mass manipulation as a training method for well-trained sprinters; however, a change in correlations between sprinting speed and technique measures should be considered during such training.